Humanistic context of foreign language education development at the Belarusian State University in 1921–1961 (to the 105th anniversary of the university’s foundation) - Trukhan, Ekaterina V. (University Pedagogical Journal, 2026)
The need for a retrospective analysis of the humanisation of foreign language education at the Belarusian State University is substantiated. For the first time, the humanistic context of foreign language education from the institutionalization of the Belarusian State University in 1921 to 1961 is examined using collected archival data. This humanisation is associated with the transformation in the goals, approaches, research aspects, and content of foreign language education. The proposed chronicle of development and historical and pedagogical analysis of the trends, characteristics, and challenges in implementing a humanistic approach to foreign language education at the Belarusian State University during this period are intended to facilitate the development of ways to achieve the personally oriented goal of foreign language education, prevent the replication of irrational actions, utilise effective resources for foreign language education, and further promote the future development of the system.
Keywords: historical development; foreign language education; humanistic approach; Belarusian State University